Deviant Desires: Libidinal Facets in Upamanyu Chatterjee’s Weight Loss - Gahlyan, Rakhee (Innovative Research Thoughts, 2018)
On the compass of Indian Writings in English, Upamanyu Chatterjee has sculpted a definite niche for himself, as the master of ludicrous, ‘the witty biographer of the misfit.’ He comes across as unapologetic in dealing with the most ‘weird and obnoxious’ in equally contemptuous and ferocious manner. His novel, Weight Loss (2006) is a dark comedy. It was subsequently nominated by India International Centre Library, New Delhi for the International IMPAC Dublin Literary Award for 2008. The novel projects the life of unmorally crippled, unconventional, part fantasist part confused and total deviant, Bhola. He shares these qualities with the other protagonists of Chatterjee. The present paper throws light on the deviant desires of Bhola who has the perpetual wander lust for the meaning of life. The novelist displays the mental and manual endeavors of the Indian youth with all its demonstrations.